THE EFFECT OF PROJECT-BASED LEARNING THROUGH ARTIFICIAL INTELLIGENCE (AI) IN INCREASING STUDENTS' CREATIVITY AND LEARNING ACHIEVEMENT - Anita Debora Simangunsong; Hamela Sari Sitompul; Eva Pratiwi Pane; Golda Novatrasio Sauduran (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This research aims to increase student creativity and learning achievement by implementing a project-based learning model through Artificial Intelligence (AI). This research is Classroom Action Research which was carried out in two cycles. Each cycle has four stages: planning, implementation, observation, and reflection. The research subjects were 22 first semester students of FKIP, HKBP Nommensen Pematang Siantar University. Data collection techniques through observation, interviews, document studies, questionnaires and tests. The analysis technique used in this research is descriptive qualitative. In Cycle I, the percentage of student creativity reached 45.45% and increased to 86.26% in Cycle II. The percentage of completion of the student knowledge learning aspect in Cycle I was 59.09% and increased to 90.90% in Cycle II. Based on the research results, it can be concluded that the application of a project-based learning model through Artificial Intelligence (AI) can increase student creativity and learning achievement in the Basic Chemistry course for FKIP students at HKBP Nommensen University.